Sedmi mednarodni znanstveni sestanek Slovenski dialekti v stiku (2018) - Jakop, Tjaša (Slavia Centralis, 2020)
The author reports on the international scientific conference Slovene dialects in contact 7 / Dialetti sloveni in contatto 7, which took place from 23 to 24 April 2018 in Portorož.